The effect of nutritional supplementation on nutritional status, pulmonary function and quality of life among stable emphysematous patients - Librando, Ma Luisa C.
The effect of nutritional supplementation for three months on nutritional status, pulmonary function and quality of life among stable ambulatory emphysematous patients was examined. The study was a pre - post experimental design. A total of 60 patients were recruited in this study; thirty patients each were randomly assigned to either the supplement group or the regular upbuilding group. The supplement group were provided with a nutritional formula containing 500 calories, 18, 24, and 58of which were contributed by protein, fat and carbohydrate respectively. On the other hand, the regular upbuilding group was advised to increase their caloric intake equivalent to 500 calories derived from protein (15), fats (25) and carbohydrate (60). Both groups were asked to maintain their usual intake during the entire study period.The study showed that after three months of oral supplementation stable out patients had improvements in nutritional status indices such as BMI, percent standard weight and MUAC with statistically significant difference of (p0.000). Improvements in nutritional status is associated with improvement in the quality of life as measured by decreased fatigue, dyspnea and emotional dimensions. There has been statistically significant difference (p0.05) in FEV between the supplement group and the regular upbuilding group at the end of the study period. The supplement group showed negative change in pulmonary function indices while the regular upbuilding group had positive change at the end of three months. A low weigh gain was noted in the supplement group and the possible causes identified were: frequent exacerbation, taste fatigue and substitution of the supplement to the oral diet.Intakes of energy, carbohydrate, protein and fats as well as vitamins A and C of both group at the start of the study were more than the RDA. This result is in contrast with other investigators who reported low nutrient intake among COPD patients. Contrary to the previously recommended high fat diet among COPD patients, baseline intakes of both groups followed normal diet (Carbohydrate 60, protein 15and fats 25).In conclusion, nutritional supplementation produced improvements in nutritional status and quality of life among stable emphysematous out-patients but it does not change pulmonary function indices.The improvement in clinical indicators as reported y the subjects indicates that nutritional supplementation among stable emphysematous out-patients may be beneficial. Thus in the management of these patients, it is important that attention be given not only to their survival but also to the improvement of the quality of life.